Incidence of clinical and environmental vibrio parahaemolyticus isolates in Hat Yai City and biosurfactants produced by soil microorganisms against vibrio parahaemolyticus - Junthip Thongjun (Prince of Songkla University, 2014)
Thesis (Ph.D., Microbiology)--Prince of Songkla University, 2013